Capacidad predictiva del tamizaje de cardiopatías congénitas con pulso oximetría en recién nacidos de un hospital público de Loreto, 2023 - Sialer Sosa, Ricardo Arturo (2024)
GENERAL OBJECTIVE: To estimate the predictive capacity of pulse oximetry screening in newborns with congenital heart disease at the Regional Hospital of Loreto. 2023. MATERIALS AND METHODS: Quantitative, analytical and cross-sectional study. Which expects to evaluate 3000 asymptomatic newborns in the period of 1 year. It will be considered as positive pulse oximetry screening at (1) SpO2 < 90% in one limb, (2) SpO2 of 90–94% in right hand and foot in 3 measures one hour apart (3) saturation difference > 3% between the upper and lower extremity in 3 measurements one hour apart. Positive cases will be confirmed by echocardiography, which will be the gold standard. Sensitivity, specificity, positive and negative predictive value will be calculated. The analysis will be performed on the SPSS v25. CONCLUSIONS: The use of pulse oximetry has been shown to be effective, accurate and inexpensive as a screening tool for congenital heart disease at the Regional Hospital of Loreto.